2020
DOI: 10.5222/mmj.2020.92332
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Year Retrospective Analysis of Basal Cell Carcinoma: A Monocentric Study

Abstract: Objective: Our aim in this study is to define the histopathological subtypes, body site distribution, and incidence rates of single or multiple of BCCs. The study is conducted on patients from a single institution in Istanbul which has a migrant-receiving population reflecting that of the country overall. Method: We retrospectively analyzed data concerning 896 cases of BCC seen between 2014 and 2018. Data about patient demographics (age and sex), tumor diameter,its anatomic localization, histological type, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The most common pathological BCC variant in our cohort was the nodular type which is consistent with the data reported in the literature (Cameron et al 2019 ; Tan et al 2015 ; Ozkanli et al 2020 ; Muzic et al 2017 ). Regarding the giant BCC, Vaca-Aguilera et al ( 2019 ) reported that infiltrating type was the most common pathological variant.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The most common pathological BCC variant in our cohort was the nodular type which is consistent with the data reported in the literature (Cameron et al 2019 ; Tan et al 2015 ; Ozkanli et al 2020 ; Muzic et al 2017 ). Regarding the giant BCC, Vaca-Aguilera et al ( 2019 ) reported that infiltrating type was the most common pathological variant.…”
Section: Discussionsupporting
confidence: 92%
“…This could be explained in western countries by the frequent use of tanning bath by females (Kappelin et al 2022 ; Garcias-Ladaria et al 2017 ), which is not a common habit for Egyptian females due to religious and social customs. However, a Turkish study reported that females showed earlier onset of BCCs, and they share the religious customs and ethnic race with Egyptians (Ozkanli et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 80% of all BCC cases are diagnosed within the cervicofacial area [ 5 , 6 ]. Even though most periocular tumours are of a benign nature [ 7 ], BCC is the most frequent malignant periocular tumour and 10–16% of all BCCs are diagnosed on the eyelids [ 8 , 9 ]. Various subtypes of BCC have been described in the literature.…”
Section: Introductionmentioning
confidence: 99%